Image analysis of modified cellulose fibers from sugarcane bagasse by zirconium oxychloride - Mulinari, D. R.; Cruz, T. G. [UNESP]; Cioffi, M. O. H. [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP]; Da Silva, M. L. C. P.; Rocha, G. J. M. (Elsevier B.V., 2010)
Surface modification of natural fibers has been made using different methods. In this paper, cellulose fibers from sugarcane bagasse were bleached and modified by zirconium oxychloride in situ. The chemically modified cellulose fibers were compared to those of bleached ones. Cellulose fibers were modified with ZrO(2)center dot nH(2)O nanoparticles through the use of zirconium oxychloride in acidic medium in the presence of cellulose fibers using urea as the precipitating agent. The spatial distribution characterization of hydrous zirconium oxide on cellulose fibers was carried out by combining both processing and image analyses obtained by SEM and statistical methodologies. Scanning electron microscopy (SEM), X-ray diffraction (XRD), and thermogravimetric analysis (TG) were also used to characterize the nanocomposite. Results indicated that ZrO(2)center dot nH(2)O nanoparticles of about 30-80 nm diameter deposited on cellulose fibers were heterogeneously dispersed. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Sugarcane bagasse; ZrO(2)center dot nH(2)O nanoparticles; Nanocomposite